Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Matematika Kelas IV SDN Minasa Upa Kecamatan Rappocini Kota Makassar - Sahrina Said; Mukhlis Mukhlis; Andi Ardhilah Wahyudi (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
The type of research used in this study was Classroom Action Research (CAR), which consisted of two cycles, each cycle consisting of 4 meetings. Research procedures include planning, implementing actions, observation, and reflection. The subjects in this study were 32 students of class IV at SDN Minasa Upa, Rappocini District, Makassar City. The results showed that in the first cycle, out of 32 students, only 18 students or 56.2% completed individually, where an average score of 62.8 was obtained with 4 students very critical (12.5%), 4 students critical (12, 5), 10 students are quite critical (31.2%), and 14 students are less critical (43.7%). Whereas in cycle II which was completed individually of 32 students there were 25 students or 78.1%, where an average value of 75.7 was obtained with 13 students very critical (40.6%), 5 students critical (15.6%) , 7 students are quite critical (21.8), and 7 students are less critical (21.8). Based on the results of this study, it can be concluded that students' critical thinking skills in mathematics class IV at SDN Minasa Upa, Rappocini District, Makassar City through the application of the Problem Based Learning (PBL) model have increased.